Etiology and Diagnosis of Obstructive Jaundice, Our Experience (Medical Forum Monthly, 2024)
Introduction: Obstructive jaundice is a common problem faced by surgeons.Objectives: To ascertain various etiologies of obstructive jaundice in our set up and to evaluate the usefulness of available diagnostic modalities.Study Design: Descriptive Study. Place and Duration of study: This study was conducted at Allied and District Head Quarter Hospital, Faisalabad from April 2010 to Sep. 2010.Materials and Methods: Eighty-five patients with obstructive jaundice were included in the study. They were evaluated on the basis of history, clinical examination, biochemical tests and ultrasonography. CT scan abdomen was done in suspected malignant cases only. Operative findings were compared with preoperative ultrasound and CT scan findings. The results were then prepared and analyzed.Results: In our study, 56.5% patients were of benign etiology and 34.5% were of malignant etiology. Female to male ratio was 2:1. Serum bilirubin was raised more in malignant diseases than in benign diseases. An accuracy of 80% of ultrasound and 86% of CT scan abdomen was found out after performing different surgical procedures in our patients. In benign group of patients the most common cause was choledocholithiasis, 47.1% while in malignant group the most common cause was carcinoma of head of pancreas, 34.1%. Conclusion: Common causes of obstructive jaundice in our study were choledocholithiasis and carcinoma head of pancreas. Ultrasound is a reliable tool for diagnosis of obstructive jaundice, and CT scan is helpful in evaluation of malignancy.